Application of Field Trip Method to Support Elementary School Children In Learning Sains Material Of Living Things - Febrina Siska Widyaningtyas; Rahma Dyani Jelang Syafitri; Desy Septia Kartikasari; Dora Natasya Napitupulu; Anisa Uswatun Khasanah (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
Informal learning that takes place in the family environment is very important for children. Moreover, children's basic understanding and experience of living things around them by using the environment as a medium is a provision for continuing formal education. This is in line with the research objectives, namely to determine the application of the field trip method to support elementary school children's learning in understanding science material with a focus on animals as living things. This research uses a qualitative approach with descriptive methods. The data collection method is through observation, interviews, and documentation. Meanwhile, the stages of data analysis techniques include data reduction, data exposure, and conclusion drawing as well as verification. The research subjects were parents and children. The researcher also observed one of the educational tourist attractions in Yogyakarta as a family target in supporting informal learning, namely Gembira Loka zoo. The results of the observation stated that in the Gembira Loka zoo in Yogyakarta there were facilities and rides that could be used by visitors, especially parents and children, in learning science. On the other hand, from the interview, it was found that the field trip method to Gembira Loka zoo fully supports informal learning because it provides meaningful understanding and direct experience to children. Thus, this research can be a reference for families to apply the field trip method in learning science.